Robo de néctar en Campsidium valdivianum: observaciones sobre la morfología floral y el papel de abejorros y aves en el sur de Chile - Valdivia Prats, Carlos E. (2025)
In the temperate forests of Chile and Argentina, many plants are pollinated by the hummingbird Sephanoides sephaniodes. One such plant is the vine Campsidium valdivianum. In Argentina, the native bumblebee Bombus dahlbomii robs nectar from C. valdivianum flowers, showing a preference for those with longer corollas. In Chile, C. valdivianum flowers exhibit both small and large perforations, suggesting a greater diversity of nectar robbers. In the study area, nectar robbery could be attributed to native and exotic bumblebees (B. dahlbomii and Bombus terrestris), which are likely responsible for the small perforations, whereas native birds (Phrygilus patagonicus and Elaenia albiceps) are probably responsible for the large perforations. We hypothesized that plants with longer and narrower flowers would experience higher levels of nectar robbery, by both bumblebees and birds, compared to those with shorter and wider flowers. We evaluated the effects of corolla length, width, and variability among individual plants on the incidence of small and large perforations. We found that 6.7% of flowers exhibited small perforations, while 14.8% showed large perforations. Corolla length was not significantly correlated with the occurrence of either type of perforation. However, birds appeared to differentiate among individual plants based on factors not addressed in this study. Understanding the frequency and causes of nectar robbery is essential for advancing knowledge of the ecology and evolution of floral traits in hummingbird-pollinated plants of the temperate forests of South America.